Sauber recyceln- Innovative Verfahrenskombination mit Ultraschall ermöglicht sicheren Umgang mit recycelten Carbonfasern - Linnig, Caterina; Tröster, Thomas (CU reports)

The environmental impact on the strain rate dependent energy absorption capability of a hybrid crash absorber element - Haller, Sebastian; Tinkloh, Steffen Rainer; Tröster, Thomas; Brandt, Robert (5th International Conference Hybrid 2022 Material & Structures)

Investigation on hot sheet metal forming by means of a longitudinal flux inductor - Pfeifer, Florian; Tröster, Thomas; Marten, Thorsten; Dietrich, André; Nacke, Bernard; Grundmeier, Guido (Proceedings of the 6th International Conference on Steels in Cars and Trucks)

Ein Beitrag zur Etablierung von Holzwerkstoffen im strukturellen Automobilbau anhand der Vorentwicklung zweier Karosseriebauteile aus Rotbuche - Schweizer, Swetlana
Die überwiegende Nutzung von nachwachsenden Rohstoffen ist ein wichtiger Aspektzum dauerhaft nachhaltigen Wirtschaften. Dem Einsatz von Holzwerkstoffen in der Automobilindustriestehen u. a. immer noch zahlreiche Kenntnislücken zum Material- undzum Strukturverhalten unter z. B. dynamischer Belastung entgegen. Um den Kenntnisstandzu erweitern und das Potenzial der Holzwerkstoffe als nachhaltige Alternative zuden etablierten Werkstoffen zu veranschaulichen, wurden hier zwei Demonstratoren vonBauteilen der Fahrzeugkarosserie aus dem Furnierschichtholz (FSH) der Buche entwickeltund getestet. Die ausgewählte Stoßabsorptionsvorrichtung und die Sitzrückwandwurden unter der Berücksichtigung der auftretenden Lasten und der Materialparameterkonzeptioniert. Im Vordergrund standen bei der Stoßabsorptionsvorrichtung eine möglichsthohe Aufnahme von Crashenergie und bei der Sitzrückwand die fertigungstechnischenAspekte der Furnierumformung zu einer komplexen Geometrie. Die entwickeltenDemonstratoren erfüllten die im Rahmen dieser Arbeit an sie gestellten Anforderungenzufriedenstellend und wiesen zum Teil ein erhebliches Leichtbaupotenzial gegenüberden metallischen Referenzstrukturen auf. Mit dieser Arbeit wurden grundlegende Erkenntnisseüber das Verformungs- und Versagensverhalten von Strukturen aus FSH unterquasistatischer und dynamischer Belastung gewonnen, um so die möglichen Einsatzgebietedieses Holzwerkstoffes zu erweitern.

Haftung und Korrosionsbeständigkeit direktgefügter Hybridsysteme aus kohlenstofffaserverstärktem Epoxidharz und verzinktem Stahl für den Automobilleichtbau - Striewe, Jan Andre

Co-bonding of carbon fibre-reinforced epoxy and galvanised steel with laser structured interface for automotive applications - Voswinkel, Dietrich; Striewe, Jan Andre; Grydin, Olexandr; Meinderink, Dennis; Grundmeier, Guido; Schaper, Mirko; Tröster, Thomas (Advanced Composite Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; Ceramics and Composites

Experimental Analysis of Residual Stresses in CFRPs through Hole-Drilling Method: The Role of Stacking Sequence, Thickness, and Defects - Wu, Tao; Kruse, Roland; Tinkloh, Steffen Rainer; Tröster, Thomas; Zinn, Wolfgang; Lauhoff, Christian; Niendorf, Thomas (Journal of Composites Science)
Carbon fiber reinforced plastics (CFRPs) gained high interest in industrial applications because of their excellent strength and low specific weight. The stacking sequence of the unidirectional plies forming a CFRP laminate, and their thicknesses, primarily determine the mechanical performance. However, during manufacturing, defects, e.g., pores and residual stresses, are induced, both affecting the mechanical properties. The objective of the present work is to accurately measure residual stresses in CFRPs as well as to investigate the effects of stacking sequence, overall laminate thickness, and the presence of pores on the residual stress state. Residual stresses were measured through the incremental hole-drilling method (HDM). Adequate procedures have been applied to evaluate the residual stresses for orthotropic materials, including calculating the calibration coefficients through finite element analysis (FEA) based on stacking sequence, laminate thickness and mechanical properties. Using optical microscopy (OM) and computed tomography (CT), profound insights into the cross-sectional and three-dimensional microstructure, e.g., location and shape of process-induced pores, were obtained. This microstructural information allowed for a comprehensive understanding of the experimentally determined strain and stress results, particularly at the transition zone between the individual plies. The effect of pores on residual stresses was investigated by considering pores to calculate the calibration coefficients at a depth of 0.06 mm to 0.12 mm in the model and utilizing these results for residual stress evaluation. A maximum difference of 46% in stress between defect-free and porous material sample conditions was observed at a hole depth of 0.65 mm. The significance of employing correctly calculated coefficients for the residual stress evaluation is highlighted by mechanical validation tests.
Keywords: Engineering (miscellaneous); Ceramics and Composites

Characterization of residual stresses in fiber metal laminate interfaces - A combined approach applying hole-drilling method and energy-dispersive X-ray diffraction - Wu, T.; Degener, S.; Tinkloh, Steffen Rainer; Liehr, A.; Zinn, W.; Nobre, J.P.; Tröster, Thomas; Niendorf, T. (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Numerical investigation of the clinched joint loadings considering the initial pre-strain in the joining area - Martin, Sven; Bielak, Christian Roman; Bobbert, Mathias; Tröster, Thomas; Meschut, Gerson (Production Engineering)
The components of a body in white consist of many individual thin-walled sheet metal parts, which usually are manufactured in deep-drawing processes. In general, the conditions in a deep-drawing process change due to changing tribology conditions, varying degrees of spring back, or scattering material properties in the sheet blanks, which affects the resulting pre-strain. Mechanical joining processes, especially clinching, are influenced by these process-related pre-strains. The final geometric shape of a clinched joint is affected to a significant level by the prior material deformation when joining with constant process parameters. That leads to a change in the stiffness and force transmission in the clinched joint due to the different geometric dimensions, such as interlock, neck thickness and bottom thickness, which directly affect the load bearing capacity. Here, the influence of the pre-straining in the deep drawing process on the force distribution in clinch points in an automotive assembly is investigated by finite-element models numerically. In further studies, the results are implemented in an optimization tool for designing clinched components. The methodology starts with a pre-straining of metal sheets. This step is followed by 2D rotationally symmetric forming simulations of the joining process. The resulting mesh of each forming simulation is rotated and 3D models are obtained. The clinched joint solid model with pre-strains is used further to determine the joint stiffnesses. With the simulation of the same test set-up with an equivalent point-connector model, the equivalent stiffness for each pre-strain combination is determined. Simulations are performed on a clinched component to assess the influence of pre-strain and sheet thinning on the clinched joint loadings by using the equivalent stiffnesses. The investigations clearly show that for the selected component, the loadings at the clinch points are dependent on the sheet thinning and the stiffnesses due to pre-strain. The magnitude of the influence varies depending on the quantity considered. For example, the shear force is more sensitive to the joint stiffness than to the sheet thinning.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Influence of the Surrounding Sheet Geometry on a Clinched Joint - Martin, Sven; Kurtusic, Kristijan; Tröster, Thomas (Key Engineering Materials)

In-Mold-Assembly of Hybrid Bending Structures by Compression Molding - Stallmeister, Tim; Tröster, Thomas (Key Engineering Materials)
The further development of in-mold-assembly (IMA) technologies for structural hybrid components is of great importance for increasing the economic efficiency and thus the application potential. This paper presents an innovative IMA process concept for the manufacturing of bending loaded hybrid components consisting of two outer metal belts and an inner core structure made of glass mat reinforced thermoplastic (GMT). In this process, the core structure, which is provided with stiffening ribs and functional elements, is formed and joined to two metal belts in one single step. For experimental validation of the concept, the development of a prototypic molding tool and the manufacturing of hybrid beams including process parameters are described. Three-point bending tests and optical measurement technologies are used to characterize the failure behavior and mechanical properties of the produced hybrid beams. It was found that the innovative IMA process enables the manufacturing of hybrid components with high energy absorption and low weight in one step. The mass-specific energy absorption is increased by 693 % compared to pure GMT beams.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Advanced Automotive Components by Fiber-Metal-Laminates - Triebus, Marcel; Ostermann, Moritz; Tröster, Thomas; Horwath, Ilona (Materials in Car Body Engineering - Bad Nauheim)

Integrating Future Energy, Material and Production Scenarios in Life Cycle Engineering of Automotive Lightweight Structures - Ostermann, Moritz; Grenz, Julian; Triebus, Marcel; Cerdas, Felipe; Marten, Thorsten; Tröster, Thomas; Herrmann, Christoph (Proceedings of the 17th Conference on Sustainable Development of Energy, Water and Environment Systems)

Individualisierung des ÖPNV - Integration technischer und sozialer Dimensionen nachhaltiger Mobilität - Ostermann, Moritz; Behm, Jonathan; Marten, Thorsten; Tröster, Thomas; Weyer, Johannes; Cepera, Kay; Adelt, Fiabian (14. Wissenschaftsforum Mobilität)

Influence of laser-generated surface micro-structuring on the intrinsically bonded hybrid system CFRP-EN AW 6082-T6 on its corrosion properties - Delp, Alexander; Freund, Jonathan; Wu, Shuang; Scholz, Ronja; Löbbecke, Miriam; Haubrich, Jan; Tröster, Thomas; Walther, Frank (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Strom statt Gas: Nachhaltige Herstellung von Karosseriebauteilen - Pfeifer, Florian; Jungeilges, André; Behm, Jonathan (Transforming Economies)

Gekoppelte Simulation des resistiven Schnellerwärmens für Fertigungsprozesse mit integrierter Wärmebehandlung am Beispiel der Titanlegierung Ti-6Al-4V - Merten, Mathias; Klöppel, Thomas; Haufe, André; Kaiser, Maximilian Alexander; Wesendahl, Jan-Niklas; Konrad, Stefan (Workshop Warmblechumformung)
Der Beitrag liefert einen Überblick über die Möglichkeiten der gekoppelten multiphysikalischen numerischen Simulation mit dem Finite Elemente-Löser LS-DYNA. Am Beispiel der resistiven Schnellerwärmung einer Titanlegierung im Forschungsprojekt TISTRAQ erfolgt die Beschreibung der Vorgehensweise, der Eingangs- und Ergebnisgrößen sowie der weiteren Anwendung der Simulation im Forschungsprojekt. Im Fokus steht dabei die Ermittlung der lokalen Temperaturverläufe, deren Kenntnis eine Grundvoraussetzung für die Berechnung prozessabhängiger Materialkennwerte darstellt.

Heat transfer coefficient investigation for hot die quenching process of Ti-6Al-4V alloy - Kaiser, Maximilian Alexander; Rockicki, Pawel; Höschen, Fabian; Wesendahl, Jan-Niklas; Konrad, Stefan; Meyer, Thomas; Marten, Thorsten; Tröster, Thomas
In the aerospace industry processing of high strength titanium alloys is both resource and time consuming. That why a lot of efforts is put on development of new and highly advanced manufacturing processes as hot die quenching. The process is based on combination of elevated temperature plastic forming with modification of the microstructure due to heat treatment, and thus increase in the properties of finally shaped geometry. One of the most crucial factors in the hot die quenching process is heat transfer coefficient. It is a main driver for adjustment of basic process parameters, as selection of tool material or the strain rate, but also plays an important role while elaborating temperature field in the numerical model. Thus, the main scope of the research within the current study is to examinate the heat transfer coefficient (HTC) for titanium and tooling material, which correspond to a real forming process. New and unique test stand have been designed and presented together with preliminary experimental results, which are a basis for further numerical simulation model of the hot die quenching process.
Keywords: Ti-6Al-4V; heat transfer coefficient

Isothermal hot forming of Titanium sheet metal - From parameter identification to custom parts - Kaiser, Maximilian Alexander; Wesendahl, Jan-Niklas; Meyer, Thomas

Evaluation of the Ecological Footprint for Parts from AlSi10Mg manufactured by Laser Powder Bed Fusion - Bödger, Christian; Weiss, Christian; Schiefer, Ekkehard; Heussen, Daniel; Haefner, Constantin (Proceedings of the 33rd Annual International Solid Freeform Fabrication Symposium – An Additive Manufacturing Conference)
The manufacturing industry contributes immensely to the global emissions and therefore is a key factor that has to be addressed when a more sustainable production is desired. Laser Powder Bed Fusion (LPBF) is an AM technique that offers the possibility to manufacture metal parts in a more material efficient way due to the layer-by-layer build-up. Nevertheless, the processing chain for parts from LPBF contains additional steps like powder atomization, which also influence the ecological footprint of the production chain. Within this work, a life-cycle model for the production step of parts from AlSi10Mg powder material is developed. The model is supplied with data from the powder atomization up to the production step, either by literature, database or experimental measurements during production. The footprint in terms of CO2 emissions is then analyzed and emission-intense steps are identified. Two manufacturing scenarios are considered to evaluate the sensitivity on the emissions.

Forming Simulation of Tailored Press Hardened Parts - Triebus, Marcel; Reitz, Alexander; Grydin, Olexandr; Grenz, Julian; Schneidt, Andreas; Erhardt, Rüdiger; Tröster, Thomas; Schaper, Mirko (13th European LS-DYNA Conference 2021)

Großserientaugliche induktive Platinenerwärmung für den Warmformprozess - Tröster, Thomas; Pfeifer, Florian; Nacke, Bernard; Dietrich, André

Development of a submodel technique for FFT-based solvers in micromechanical analysis - Tinkloh, Steffen Rainer; Wu, Tao; Tröster, Thomas; Niendorf, Thomas
Keywords: Micromechanics; Fast Fourier Transform (FFT); Reduced Order Modelling; Homogenization

Development of a hybrid crash-relevant car body component with load-adapted thickness properties: Design, manufacturing and testing - Camberg, Alan Adam; Tröster, Thomas; Latuske, Clemens

A new numerical method for potential anaylsis and design of hybrid components from full vehicle simulations: Implementation and component design - Camberg, Alan Adam; Tröster, Thomas; Wingenbach, Nils; Hielscher, Christian; Grenz, Julian

A new Device for Determination of Forming-Limit-Curves under Hot-Forming Conditions - Triebus, Marcel; Gierse, Jan; Marten, Thorsten; Tröster, Thomas (IOP Conference Series: Materials Science and Engineering)

Entwicklung eines neuartigen Reinigungsverfahrens für recycelte Kohlenstofffasern - Linnig, Caterina; Tröster, Thomas

Measurement and Analysis of Residual Stresses and Warpage in Fiber Reinforced Plastic and Hybrid Components - Wu, Tao; Tinkloh, Steffen Rainer; Tröster, Thomas; Zinn, Wolfgang; Niendorf, Thomas (Metals)
Glass/carbon fiber reinforced plastic (GFRP/CFRP) and hybrid components have attracted increasing attention in lightweight applications. However, residual stresses induced in the manufacturing process of these components can result in warpage and, eventually, negatively affect the mechanical performance of the composite structures. In the present work, GFRP, CFRP, GFRP/steel and CFRP/steel hybrid components were manufactured through the prepreg-press-technology always employing the same process parameters. The residual stresses of these components were measured through the hole drilling method (HDM), based on an adequate formalism to evaluate the residual stresses for orthotropic materials including the calculation of the calibration coefficients via finite element analysis (FEA). In FEA, the real material lay-up and mechanical properties of the samples were considered. The warpage induced by residual stresses was measured after the samples were removed from the tool. The measured residual stresses and warpage of four different types of samples were compared and results were analyzed in depth. The results obtained can be extended to other hybrid materials and even could be used for designing multi-stable laminates for application in adaptive structures. Moreover, the effects of the drilling process parameters of HDM, e.g., the drilling speed, the drilling increment and the zero-depth setting, on the resulting residual stresses of GFRP were investigated. The reliability of residual stress measurements in GFRP using HDM was validated through mechanical bending tests. The conclusions concerning the choice of optimal drilling parameters for GFRP could be directly applied for other types of samples considered in the present work.

The Effect of Fiber Waviness on the Residual Stress State and Its Prediction by the Hole Drilling Method in Fiber Metal Laminates: A Global-Local Finite Element Analysis - Tinkloh, Steffen Rainer; Wu, Tao; Tröster, Thomas; Niendorf, Thomas (Metals)

On the reliability of residual stress measurements in unidirectional carbon fibre reinforced epoxy composites - Magnier, A.; Wu, T.; Tinkloh, Steffen Rainer; Tröster, Thomas; Scholtes, B.; Niendorf, T. (Polymer Testing)

HyOpt - Optimization-Based Development of Hybrid Materials - Triebus, Marcel; Tröster, Thomas (9th NRW Nano Conference - Innovations in Materials and Applications)

A Generalized Stress State and Temperature Dependent Damage Indicator Framework for Ductile Failure Prediction in Heat-Assisted Forming Operations - Camberg, Alan Adam; Erhart, Tobias; Tröster, Thomas (Materials)
Heat-assisted forming processes are becoming increasingly important in the manufacturing of sheet metal parts for body-in-white applications. However, the non-isothermal nature of these processes leads to challenges in evaluating the forming limits, since established methods such as Forming Limit Curves (FLCs) only allow the assessment of critical forming strains for steady temperatures. For this reason, a temperature-dependent extension of the well-established GISSMO (Generalized Incremental Stress State Dependent Damage Model) fracture indicator framework is developed by the authors to predict forming failures under non-isothermal conditions. In this paper, a general approach to combine several isothermal FLCs within the temperature-extended GISSMO model into a temperature-dependent forming limit surface is investigated. The general capabilities of the model are tested in a coupled thermo-mechanical FEA using the example of warm forming of an AA5182-O sheet metal cross-die cup. The obtained results are then compared with state of the art of evaluation methods. By taking the strain and temperature path into account, GISSMO predicts greater drawing depths by up to 20% than established methods. In this way the forming and so the lightweight potential of sheet metal parts can by fully exploited. Moreover, the risk and locus of failure can be evaluated directly on the part geometry by a contour plot. An additional advantage of the GISSMO model is the applicability for low triaxialities as well as the possibility to predict the materials behavior beyond necking up to ductile fracture.
Keywords: General Materials Science

Festigkeitssteigerung von Aluminiumblechformteilen der 5000-Serie durch Erweiterung der Formgebungsgrenzen stark kaltverfestigter Ausgangswerkstoffe - Camberg, Alan Adam
Leichtmetalle mit einem breiten Eigenschaftsspektrum gewährleisten die Realisierung ressourcenschonender Produkte und ermöglichen die Intensivierung sortenreiner Kreislaufwirtschaften. Die vorliegende Arbeit untersucht einen wärmeunterstützten Ansatz zur Erhöhung der Formgebungsgrenzen stark kaltverfestigter AlMg4,5 Blechwerkstoffe bei gleichzeitiger Beschränkung des Festigkeitsverlustes durch Erholungseffekte. Experimentelle Untersuchungen stellen eine wissenschaftlich fundierte Erkenntnisbasis über die werkstofftechnischen Wirkzusammenhänge des untersuchten Prozesses dar. Gepaart mit an realen Bauteilgeometrien validierten numerischen Simulationsmodellen legt diese Arbeit einen methodischen Grundstein für die industrielle Umsetzung des hier untersuchten Blechumformprozesses. Die erzielte mittlere Dehngrenze des exemplarisch untersuchten Bauteils übersteigt die Dehngrenze eines konventionellen AlMg4,5 Werkstoffes um 190 %. Mit 320 MPa entspricht sie dem Festigkeitsniveau des walzharten Blechhalbzeuges im Lieferzustand, ein Wert, der nach dem aktuellen Stand der Technik auf Bauteilebene ausschließlich mit aushärtbaren AlMgSi Legierungen darstellbar ist.
Keywords: Aluminium; Blechumformung; AlMg; Materialmodellierung; Duktiles Versagen; Halbwarmumformung; Automobil; Leichtbau; Uni-Alloy; 5000-Serie; 5182; GISSMO

Beitrag zur Reduzierung der Fehlerhäufigkeit bei der Online-Lackierung von SMC-Außenhautbauteilen - Huber, Johannes
Der Verbau von Sheet Moulding Compounds im automobilen Außenhautbereich führt in der industriellen Praxis regelmäßig zu abnehmenden Direktläuferquoten in der Technologie Oberfläche, denn neben bekannten Lackierfehlern ergeben sich auch werkstoff-spezifische Oberflächendefekte, welche einen Bauteilwechsel bedingen. Die hier vorliegende Arbeit soll einen aktiven Beitrag zur Reduzierung von Ausschuss und Nacharbeit entlang der Lackierprozesskette leisten. Zu Beginn werden die erfolgskritischen Oberflächendefekte identifiziert und die zugehörigen Fehlerursachen ermittelt, ehe anschließend die Entwicklung der Fehlstellengrößen in Folge der Temperaturbelastung während der Trocknerdurchfahrten untersucht wird. Ferner soll die Auswirkung einer zusätzlich applizierten Oberflächengrundierung auf die Fehlerhäufigkeit sowie die Oberflächengüte im decklackierten Zustand geprüft werden. Als weitere Möglichkeit zur Problemlösung wird eine in den Prozessablauf integrierte Qualitätskontrolle gesehen, weshalb in dieser Arbeit ebenso die Eignung bekannter zerstörungsfreier Prüfmethoden für die präventive Fehlererkennung überprüft und ein zweistufiges Prüfkonzept erarbeitet wird. Das Aufzeigen möglicher Handlungsalternativen sowie die kostentechnische Gegenüberstellung der verschiedenen Anbauvarianten runden die Arbeit ab.
Keywords: Sheet Moulding Compounds; SMC; Online-Lackierung

Konzeptionierung und Auslegung eines Vorderachsträgers in hybrider Leichtbauweise im C-Segment - Pöhler, Simon
Im Rahmen dieser Arbeit wurde ein neuartiger Achsträger in hybrider Bauweise entwickelt und untersucht. Dieser besteht aus einer metallischen Oberschalenstruktur und einer mit Rippen ausgeformten glasfaserverstärkten thermoplastischen Unterschale (GMT), welche zur Einstellung der optimalen Steifigkeit dient. Die Rippen und Unterschale werden hierzu in einem Fließpressverfahren entweder gemeinsam als ein Bauteil oder als separate Einzelteile hergestellt. Durch den lokalen Einsatz von Faserverbundwerkstoffen in der Unterschale und der Rippenstruktur wird ein signifikanter Gewichtsvorteil gegenüber einer Referenzstruktur aus Stahl erzielt. Durch die Verwendung des GMT-Unterbodenschutzes konnten zudem die akustischen Eigenschaften des Fahrwerks hinsichtlich der Dämpfung positiv beeinflusst werden. Die hohen Anforderungen bzgl. Steifigkeit, Festigkeit und Beständigkeit der sicherheitsrelevanten Fahrwerkskomponente konnten unter Einhaltung des Bauraums erfüllt werden. Gleichzeitig konnte das Gesamtgewicht der Komponente im Vergleich zur klassischen Referenzstruktur um 30 % reduziert werden.
Keywords: hybrider Achsträger; Leichtbau; Hybridsysteme

Load Path Transmission in Joining Elements - Steinfelder, Christian; Martin, Sven; Brosius, Alexander; Tröster, Thomas (Key Engineering Materials)
The mechanical properties of joined structures are determined considerably by the chosen joining technology. With the aim of providing a method that enables a faster and more profound decision-making in the spatial distribution of joining points during product development, a new method for the load path analysis of joining points is presented. For an exemplary car body, the load type in the joining elements, i.e. pure tensile, shear and combined tensile-shear loads, is determined using finite element analysis (FEA). Based on the evaluated loads, the resulting load paths in selected joining points are analyzed using a 2D FE-model of a clinching point. State of the art methods for load path analysis are dependent on the selected coordinate system or the existing stress state. Thus, a general statement about the load transmission path is not possible at this time. Here, a novel method for the analysis of load paths is used, which is independent of the alignment of the analyzed geometry. The basic assumption of the new load path analysis method was confirmed by using a simple specimen with a square hole in different orientations. The results presented here show a possibility to display the load transmission path invariantly. In further steps, the method will be extended for 3D analysis and the investigation of more complex assemblies. The primary goal of this methodical approach is an even load distribution over the joining elements and the component. This will provide a basis for future design approaches aimed at reducing the number of joining elements in joined structures.

Joint point loadings in car bodies – the influence of manufacturing tolerances and scatter in material properties - Martin, Sven; Tröster, Thomas (ESAFORM 2021)

Experimental investigation on lightweight potentials of fiber-metal-laminates for automotive battery cases - Stallmeister, Tim; Martin, Sven; Marten, Thorsten; Tröster, Thomas

A Generalized Stress State and Temperature Dependent Damage Indicator Framework for Ductile Failure Prediction in Heat-Assisted Forming Operations - Camberg, Alan Adam; Erhart, Tobias; Tröster, Thomas (Materials)
Heat-assisted forming processes are becoming increasingly important in the manufacturing of sheet metal parts for body-in-white applications. However, the non-isothermal nature of these processes leads to challenges in evaluating the forming limits, since established methods such as Forming Limit Curves (FLCs) only allow the assessment of critical forming strains for steady temperatures. For this reason, a temperature-dependent extension of the well-established GISSMO (Generalized Incremental Stress State Dependent Damage Model) fracture indicator framework is developed by the authors to predict forming failures under non-isothermal conditions. In this paper, a general approach to combine several isothermal FLCs within the temperature-extended GISSMO model into a temperature-dependent forming limit surface is investigated. The general capabilities of the model are tested in a coupled thermo-mechanical FEA using the example of warm forming of an AA5182-O sheet metal cross-die cup. The obtained results are then compared with state of the art of evaluation methods. By taking the strain and temperature path into account, GISSMO predicts greater drawing depths by up to 20% than established methods. In this way the forming and so the lightweight potential of sheet metal parts can by fully exploited. Moreover, the risk and locus of failure can be evaluated directly on the part geometry by a contour plot. An additional advantage of the GISSMO model is the applicability for low triaxialities as well as the possibility to predict the materials behavior beyond necking up to ductile fracture.

Soft-magnetic behavior of laser beam melted FeSi3 alloy with graded cross-section - Andreiev, Anatolii; Hoyer, Kay-Peter; Dula, Dimitri; Hengsbach, Florian; Haase, Michael; Gierse, Jan; Zimmer, Detmar; Tröster, Thomas; Schaper, Mirko (Journal of Materials Processing Technology)

Parameter- und Prozessoptimierung für den additiven Fertigungsprozess im Pulverbett am Beispiel der Legierung Ti6Al4V - Ahlers, Dominik
Die additive Fertigung mittels Laser Powderbed Fusion Verfahren (L-PBF) von Metallen wird zunehmend genutzt, um Funktionsbauteile endkonturnah zu fertigen. Die in der vor-liegenden Arbeit untersuchte Parameter- und Prozessoptimierung liefert einen Beitrag zur wirtschaftlichen Nutzung des L-PBF und zeigt, dass höhere Aufbauraten bei der ganzheit-lichen Betrachtung des Prozesses realisierbar sind. Die Parameter- und Prozessoptimierung erfordert eine Untersuchung des Einflusses der Fertigungs- und Nachbearbeitungsparameter auf das erzeugte Volumen sowie auf die Mikrostruktur und die resultierenden Materialeigenschaften. Das Ziel der vorliegenden Arbeit ist die Entwicklung einer optimierten Prozessführung mit abschließender Bewer-tung der Wirtschaftlichkeit. Mit dem entwickelten Gesamtprozess wird eine um den Faktor 1,6 höhere Aufbaurate erzielt. Des Weiteren wird die Methodik zur Erarbeitung des opti-mierten Prozessfensters beschrieben, sodass die Herangehensweise auf weitere Werk-stoffe angewendet werden kann. Die mechanischen Eigenschaften werden für den stati-schen und dynamischen Lastfall untersucht und mit der Mikrostruktur korreliert. Abschlie-ßend wird die Prozessoptimierung zur Fertigung eines Demonstrators eingesetzt und wirtschaftlich validiert. Die Ergebnisse zeigen, dass durch das hier angewendete Vorge-hen eine Prozesszeitreduktion von 22,5% und eine Kostenreduktion von 11% realisiert werden kann.
Keywords: Additive Manufacturing; SLM

Ansatz zur effizienteren Auslegung von Hybridbauteilen - Hielscher, Christian; Grenz, Julian; Camberg, Alan Adam; Wingenbach, Nils (ATZ - Automobiltechnische Zeitschrift)

Approach to More Efficient Design of Hybrid Components - Hielscher, Christian; Grenz, Julian; Camberg, Alan Adam; Wingenbach, Nils (ATZ worldwide)

Residual stress measurement in GFRP/steel hybrid components - Wu, Tao; Tinkloh, Steffen Rainer; Tröster, Thomas; Zinn, Wolfgang (Proceedings of the 4th International Conference Hybrid 2020 Materials and Structures)

A simplified method for the evaluation of the layer compression test using one 3D digital image correlation system and considering the material anisotropy by the equibiaxial Lankford parameter - Camberg, Alan Adam; Tröster, Thomas

Predicting fracture at non-isothermal forming conditions: A temperature dependent extension of the LS-DYNA GISSMO fracture indicator framework - Camberg, Alan Adam; Erhart, Tobias; Tröster, Thomas

Wood-based materials as a sustainable alternative for future car body construction - Schweizer, Swetlana; Akbulut Irmak, Emine Fulya; Tröster, Thomas

A Holistic Approach to Optimization-Based Design of Hybrid Materials - Triebus, Marcel; Tröster, Thomas (Proceedings 4th International Conference Hybrid Materials & Structures)

Reduction of systematic measurement deviation in acoustic absorption measurement systems - Claes, Leander; Baumhögger, Elmar; Rüther, Torben; Gierse, Jan; Tröster, Thomas; Henning, Bernd (Fortschritte der Akustik - DAGA 2020)

Numerical investigation of the hole-drilling method applied to intrinsic manufactured metal-CFRP hybrids - Tinkloh, Steffen Rainer; Wu, Tao; Tröster, Thomas; Niendorf, Thomas (Proceedings of the 4th International Conference Hybrid 2020 Materials and Structures)